You are on page 1of 7

2010

1 1 ,2 A, B B 1 ,2 C , D

B 1 ,2 E , F CF 1 ,2 P, Q M , N
PB QB CD = EF C , F , M , N

AC , AD, AE , AF , DF ADB = AFBACB = AEF CD = EF


ACD AEF AD = AFADC = AFE ADF = AFD
ABC = AFD = ADF = ABF

AB CBF
CM , FN M PB CM DCF

FN CFB BA, CM , FN I 1
2 CI IM = AI IB AI IB = NI IF NI IF = CI IM

C , F , M , N

2010 1 7

2 k 3 {an } ak = 2k n > k
a + 1, a n 1n
a n = n 1
a n 1n
2 n,

{an an 1}

al = 2ll k p l 1

1, 1 i < p,
(l 1, i ) =
i = p.
p,

1, 1 i < p,
(2l + i 2, l + i 1) =
i = p.
p,

2l + i 1, 1 i < p,
al +i 1 =
i = p.
2l + 2 p 2,

al + p 1 al + p 2 = (2l + 2 p 2) (2l + p 2) = p al + p 1 = 2(l + p 1)


l k al = 2l al + p 1 al + p 2 = p l 1

2010 2 7

3 a, b, c 1 z az 2 + bz + c 1 | bc |

f ( z ) = az 2 + bz + c ,

g ( z ) = z 2 f ( z ) = a + bz 1 + cz 2 ,

h( z ) = e i g (e i z ) = c z 2 + bz 1 + a
, c , b 0 r 1

1
h(re i ) Im h(re i ) = r 2 c sin 2 + r 1b sin + Im a
2
r
Im c 0 0 < <
3

1
r 2 c sin 2 + r 1b sin 2r 2
2
r

bc = bc

bc

bc sin 2 sin

1

, r 1 , 0, ,
4r sin 2 sin
2

1
1
= min


0 , 4 sin 2 sin
r 1 , 0 , 4r sin 2 sin
min

1
3 3
=

4 max sin 2 sin


16

0 ,

| bc |=

3 3
2 2
6
3 2
f ( z ) =
z = re i , r 1
z
z
16
8
4
8
2

) (

2
2
1 2
r cos 2 2 3r cos 3 + r 2 sin 2 2 3r sin

32
2
1 4
=
2r + 12r 2 + 18 2 3r cos + r 2 3

32
1

(2r 4 + 12r 2 + 18) 1 .


32

f ( e i ) =

2010 3 7

4 m, n 1 a1 < a2 < " < am


T

| T | 1 +

am a1

2n + 1

i {1,2,", m} t T s [n, n] ai = t + s

a1 = aa m = b b a = (2n + 1)q + r q, r Z 0 r 2n
T = {a + n + (2n + 1)k | k = 0,1, ", q} | T |= q + 1 1 +

ba

2n + 1

B = {t + s | t T , s = n,n + 1,", n} = {a, a + 1,", a + (2n + 1)q + 2n}


a + (2n + 1)q + 2n a + (2n + 1)q + r = b ai B

2010 4 7

5 A1 , A2 ,", An O n 3
1 Ai 3 3 Ai 1 , Ai +1 O
A0 = AnAn +1 = A1

2 O n n A1 , A2 ,", An
n + 1 n 2 + 3n + 1
n + 1

n 2 + 3n + 1 Ai
3 Ai (1) O
1(1)(1) Ai

2 O n 2 + n + 1 O n + 1 (2) Ai
n + 1 Ai n + 1 O
n + 1
A1 , A2 , " , An O

G = { Ai , Ai +1 ," , Ai +l 1 },1 i n,1 l n j > n A j = A j n


G G (1)G
n + 1 a1 , a 2 , " , a n A1 , A2 , " , An ai n + 1, i = 1,2,", n
G = { Ai } ai n + 4 G = { Ai , Ai +1 }
ai , ai +1 n + 3 l 3 l n 1 G = { Ai , Ai +1 ,", Ai +l 1 }
ai , ai +l 1 n + 3 a j n + 2 i + 1 j i + l 2 n G = { A1 , A2 ,", An }
a j n + 2, 1 j n O n + 1

a1 + a 2 + " + a n n 2 + 2n + 1
ai {n + 1, n + 2, n + 3} Ai
ai n + 4 G = { Ai } a1 , a 2 , ", a n x n + 1 y n + 2 z n + 3
x z n 2 + 2n + 1 > n(n + 2) z 1 z = 1 x 1 ai n + 2

G = { A1 , A2 ,", An } z 2 n + 3 z z
z n + 1
x z A1 , A2 , ", An
x(n + 1) + y (n + 2) + z (n + 3) ( x + y + z )(n + 2) = n(n + 2) < n 2 + 2n + 1
O n + 1 A1 , A2 , ", An
(1) O n + 1 A1 , A2 , ", An
n + 1

2010 5 7

6 a1 , a2 , a3 , b1 , b2 , b3
(n + 1)a1n + na 2n + (n 1)a3n
(n + 1)b1n + nb2n + (n 1)b3n
n k bi = kai i = 1,2,3

r p

p > (a1r + a 2r + a3r )(b1r + b2r + b3r )

(1)

p (1) ( p, a1r + a 2r + a3r ) = 1 p p 1


n

n r (mod p 1)
n(a1r + a 2r + a3r ) + a1r a3r 0 (mod p)

(2)
(3)

(2),(3) Fermat

(n + 1)a1n + na 2n + (n 1)a3n n(a1r + a 2r + a3r ) + a1r a3r 0 (mod p)

(4)

(n + 1)b1n + nb2n + (n 1)b3n 0 (mod p)


(2) Fermat

n(b1r + b2r + b3r ) + b1r b3r 0 (mod p)

(5)

(4),(5) n

(a1r + a 2r + a3r )(b1r b3r ) (b1r + b2r + b3r )(a1r a3r ) (mod p)

(6)

(1),(6) (a1r + a 2r + a3r )(b1r b3r ) = (b1r + b2r + b3r )(a1r a3r )

(a 2 b1 ) r + 2(a3b1 ) r + (a3 b2 ) r = (a1b2 ) r + 2(a1b3 ) r + (a 2 b3 ) r

(7)

x1 ," , x s , y1 ," , y s 0 < x1 x 2 " x s , 0 < y1 y 2 " y s


r x1r + x 2r + " + x sr = y1r + y 2r + " + y sr xi = y i ( i = 1,2,", s )
s s = 1 r = 1 x1 = y1 s = t
2010 6 7

s = t + 1 xt +1 y t +1 xt +1 < y t +1
r

x1
x
y
y

+ " + t +1 = 1 + " + t + 1 1
y t +1
y t +1
y t +1
yt +1
0 <

xi
< 1 (1 i t + 1) r + 0 1 xt +1 = y t +1
y t +1

x1r + " + xtr = y1r + " + ytr , r = 1,2," xi = y i (i = 1,2,", t )


s

a1 , a 2 , a3 , b1 , b2 , b3

a 2 b1 a3 b1a3 b1 a3b2a1b2 a1b3a1b3 a 2 b3a 2 b1 a 2 b3


(7)

a 2 b1 = a3 b2 = a1b3a3 b1 = a1b2 = a 2 b3

(8)

a 2 b1 = a1b2a3 b1 = a1b3a3 b2 = a 2 b3

(9)

(8)

a
a 2 b1 a3 b2 a1b3
a
a
2 = 3 = 1 a1 , a 2 , a3
=
=
a3b1 a1b2 a 2 b3
a3 a1 a 2

(9)

b1 b2 b3
b
k
k
1 = , (k , l ) = 1, l 1 bi = aii = 1,2,3
=
=
a1 a 2 a 3
l
a1 l

2b1 + b2 =

k
k
(2a1 + a 2 ) n = 1 2a1 + a 2 2b1 + b2 l = 1
l
l

bi = kaii = 1,2,3

2010 7 7